Molecular mechanisms of sacubitril/valsartan in cardiac remodeling - Mustafa, Nor Hidayah; Jalil, Juriyati; Zainalabidin, Satirah; Saleh, Mohammed S.M.; Asmadi, Ahmad Yusof; Kamisah, Yusof (Frontiers in Pharmacology, 2022)
Cardiovascular diseases have become a major clinical burden globally. Heart failure is one of the diseases that commonly emanates from progressive uncontrolled hypertension. This gives rise to the need for a new treatment for the disease. Sacubitril/valsartan is a new drug combination that has been approved for patients with heart failure. This review aims to detail the mechanism of action for sacubitril/valsartan in cardiac remodeling, a cellular and molecular process that occurs during the development of heart failure. Accumulating evidence has unveiled the cardioprotective effects of sacubitril/valsartan on cellular and molecular modulation in cardiac remodeling, with recent large-scale randomized clinical trials confirming its supremacy over other traditional heart failure treatments. However, its molecular mechanism of action in cardiac remodeling remains obscure. Therefore, comprehending the molecular mechanism of action of sacubitril/valsartan could help future research to study the drug's potential therapy to reduce the severity of heart failure.